The Influence of Capital Structure, Profitability, Liquidity, and Company Size on the Value of Technology Sector Companies Listed on the Indonesia Stock Exchange during 2021-2024 - Nasutiah Nasutiah; Muhammad Rizal; Ngadi Permana (Pusat Riset dan Inovasi Nasional, 2025)
This study was conducted to analyze the impact of capital structure (DER), profitability (ROA), liquidity (CR), and firm size (SIZE) on firm value (PBV) in 22 companies operating in the technology sector listed on the Indonesia Stock Exchange (IDX) from 2021 to 2024. The technology sector in Indonesia faces various major challenges due to intense competition and the need for innovation, which leads to high stock price fluctuations. Therefore, firm value is a major factor that the market pays attention to. The purpose of this study is to examine and analyze the partial and simultaneous impact of capital structure, profitability, liquidity, and firm size on firm value. The methodology used is a quantitative approach with panel data regression analysis, and the Random Effects Model (REM) was chosen as the most appropriate estimation model. The main results of this study indicate that capital structure has a positive relationship and has a significant influence on firm value. On the other hand, profitability has a significant but negative influence on firm value. Meanwhile, liquidity and firm size do not show a significant influence partially on firm value. And simultaneously, capital structure, profitability, liquidity, and firm size have a significant influence on firm value. In conclusion, firm value in the technology sector during the 2021–2024 period is mainly influenced by capital structure and profitability, although overall, the four independent variables are only able to explain 7.55% of the variation in firm value, while the remaining 92.45% is influenced by factors outside this model